Design and implementation of two-wheeled self-balancing mobile robot control system based on STM32-MAT and Android - Zhai, Wenzheng; Dong, Liangwei (Journal of Measurements in Engineering, 2025)
A two-wheeled self-balancing mobile robot (TWBMR) represents a complex motion control system characterized by multi-variable, nonlinear, high-order, strong-coupling dynamics, and intrinsic instability. Aiming at the complexity of system development, this paper proposes an embedded software development approach based on model-based design (MBD) using Matlab/Simulink. By integrating a control strategy that combines a digital motion processing (DMP) attitude solver with a PID control algorithm, and leveraging the Android platform along with a Bluetooth communication module for online parameter tuning, effective self-balancing control of the TWBMR is achieved. Experimental results demonstrate that the system exhibits high accuracy in Bluetooth-based data transmission and reception, excellent control precision, robust system stability, and rapid time response. The main contribution of this paper is to make focus on concretely building a unique model architecture of the TWBMR control system able to implement all the major aspects of MBD methodology such as executable requirements and Processor-In-the Loop (PIL) simulation modes, verification and automatic code generation. It is a great advantage to develop the system faster and more efficiently, shorten the prototyping process.